Patterns of transition to employment: Comparing two generations of workers in Portugal - Oliveira, Bruno M.; Ramos, S.; Suleman, F. (Taking Inequality Seriously: Economy and Society in the Age of Inequalities, 2018)
Available literature noticed that the labour market has generated market winners, those who have access to good jobs, and market losers, who face a large decline in job quality. This duality has raised concerns among researchers and policy makers about the patterns of transition of young people to the labour market. Mostly, they are apprehensive with the particularly negative and persistent effects of precarious jobs on young workers’ professional and personnel life. However, current research has failed to find consistent evidence of possible generational differences in the distribution of workers among segments. Our research compares the transitions patterns of two generations of workers, the Xers (those who were born in 1963 – 1980) and the Millennials (those who were born in 1981 – 1996). We interviewed 19 people in Lisbon to find their occupational trajectory since the first entry to the labour market. We found four paths of transitions for Millennials and two paths for Xers. Although the Xers have been affected by reforms of regulation allowing the use of flexible arrangements, they were less likely to be assigned to precarious jobs, while the job precariousness is a regular feature of Millennials’ transition. Although some Xers move through temporary contracts, they were unlikely to have unemployment spell. The temporary jobs represented a stepping stone to permanent job for Xers. The Millennials mostly report unemployment spells in the transition from one temporary contract to another. The findings suggest that the Millennials are at risk of being entrapped in low quality jobs.